P1-S2.62 Factors associated with high-risk penetrative sex in a cohort of treatment experienced HIV-positive men who have sex with men (MSM) in British Columbia. (10th July 2011) - Michelow, W; Talany, G; O'Brien, N; Wang, H; Forrest, J; Palmer, A; Montaner, J S G; Hogg, R
Abstract : Background: In Canada, men who have sex with men (MSM) are disproportionately infected with HIV. Despite much evidence demonstrating the secondary preventive value of HAART, we have not fully capitalised on potential synergies between treatment and prevention. This study investigates high-risk sexual behaviour among treatment-experienced MSM in British Columbia, Canada. Methods: We analysed data from the Longitudinal Investigations into Supportive and Ancillary Health Services (LISA) project on MSM (gay, bisexual, or reported sex with men in the 6 months prior to interview). High-risk sexual behaviour was penetrative anal or vaginal sex in the 6 months prior to interview with less than 100% condom use. Multivariate logistic regression was used to identify factors associated with high-risk penetrative sex. Results: Of 346 HIV-positive MSM, median age was 46 years, 268 (78%) were currently on HAART, with 185 (54%) having ≥350 CD4 cells/μl. Ninety-eight (28%) participants endorsed seeking out HIV-positive partners for sex, and 147 (43%) reported being less likely to use a condom with an HIV-positive partner. In the regression model, HIV-positive MSM with a CD4 count ≥350 cells/μl were more likely to report unprotected penetrative sex (Adjusted OR [AOR] =2.7; 95% CI 1.5 to 5.2), more likely to not use condoms with their HIV-positive partners (AOR=12.0; 95% CI:6.4 to 22.3), and less likely to report sex with anonymous partners in the past 6 months (AOR=0.28; 95% CI 0.1 to 0.8). No significant associations were found between high-risk penetrative sex and current HAART use, viral suppression, or treatment adherence. Conclusion: HIV-positive MSM who report engaging in high-risk penetrative sex are more likely to be healthier (higher CD4 counts), to have unprotected sex with other HIV-positive partners (serosorting) and with known rather than anonymous sex partners. Despite healthier MSM reporting more high-risk sex, results suggest this risk-taking is discriminate and would not necessarily lead to more onward HIV transmission.